(untitled) (Acta Scientiarum. Technology, 2021)
Intermittent microwave drying improves the quality of the dehydrated product, because reduces the effect of microwave hot spots. Mathematical modelling is essential to understand the physics of this drying process and to optimize the operation conditions. However, there are few modelling studies about intermittent microwave drying. This work proposed a mathematical model based on mass balances of liquid and vapor water in which a non-equilibrium formulation described the water phase change. The microwave heating, described by Lambert´s law, was accounting as source term on the thermal energy conservation equation. The numerical solution used the finite element method, and the experimental drying of potato samples validated the simulated drying. The values of moisture content and temperature obtained by numerical solution of the model showed good agreement with experimental data. From this, it was observed the presence of three periods in the drying kinetics: an initial heating phase almost without drying, follow by a phase with constant drying rate, and final a decrease of drying rate and temperature increasement. The model results showed that the interior temperature was higher than the surface temperature of sample, and there was water evaporation inside the potato. In additional, the gradients of temperature were reduced due to intermittency of the microwave power. This redistribution of temperature could contribute to the improvement of product quality during drying.